Polyimide precursor composition, polyimide film, laminate, electronic device, method for manufacturing laminate, method for manufacturing polyimide film, and method for manufacturing electronic device

By using a polyimide precursor composition with a specific structure, including zeta structure and fluorine atom groups, the problems of transparency and internal stress of polyimide films in electronic devices are solved, realizing a polyimide film with high transparency and low stress, suitable for substrate materials of notchless displays and transparent displays.

CN120858128APending Publication Date: 2025-10-28KANEKA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480017049.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-08
Filing Date
2024-03-05
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing technologies struggle to reduce the internal stress at the interface between the polyimide film and the support while maintaining the heat resistance and transparency of polyimide, thus limiting its application in electronic devices.

Method used

A polyimide precursor composition with a specific structure, containing a specific zeolite structure and fluorine atom groups, improves transparency and reduces internal stress by adjusting the ratio of structural units and the selection of organic solvents, thereby forming a polyimide film.

Benefits of technology

It achieves high transparency and low internal stress in polyimide films, making them suitable for use in electronic devices, especially as substrate materials for notchless and transparent displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005582203950000031
    Figure BDA0005582203950000031
  • Figure BDA0005582203950000041
    Figure BDA0005582203950000041
  • Figure BDA0005582203950000051
    Figure BDA0005582203950000051
Patent Text Reader

Abstract

The polyimide precursor composition includes a polyimide precursor and an organic solvent. The polyimide precursor has a structural unit into which a specific xanthene structure is introduced. The polyimide precursor has an imidization rate of 10 mol% or more and 100 mol% or less. It is preferable that, as the organic solvent, at least one substance selected from the group consisting of N-methyl-2-pyrrolidone, 1-butyl-2-pyrrolidone, 3-methoxy-N, N-dimethyl propionamide, 3-butoxy-N, N-dimethyl propionamide, N, N-dimethyl propionamide, N, N-diethyl formamide, and 1, 3-dimethyl-2-imidazolinone is selected, preferably, as the organic solvent, at least one substance selected from the group consisting of N-methyl-2-pyrrolidone, 1-butyl-2-pyrrolidone, 3-methoxy-N, N-dimethyl propionamide, 3-butoxy-N, N-dimethyl propionamide, 3-butoxy-N, N-dimethyl propionamide, N, N-dimethyl propionamide, N, N-dimethyl propionamide, and 1, 3-dimethyl-2-imidazolinone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polyimide precursor compositions, polyimide films, laminates, electronic devices, methods for manufacturing laminates, methods for manufacturing polyimide films, and methods for manufacturing electronic devices. Background Technology

[0002] With the rapid advancements in electronic devices such as liquid crystal displays (LCDs), organic EL displays (OLEDs), electronic paper displays, solar cells, and touch panels, the trend towards thinner, lighter, and more flexible devices is underway. In these electronic devices, polyimide is being used instead of glass substrates as the substrate material.

[0003] In these electronic devices, various electronic components, such as thin-film transistors and transparent electrodes, are formed on the substrate. The formation of these electronic components requires high-temperature processes. Polyimide has heat resistance that can fully withstand high-temperature processes, making it suitable as a substrate material for flexible displays and other similar applications.

[0004] Typically, aromatic polyimides are colored yellowish-brown through the formation of intramolecular conjugation and charge transfer (CT) complexes. However, in top-emitting organic ELs and the like, since light is drawn from the opposite side of the substrate, the substrate is not required to be transparent, and conventional aromatic polyimides are used. However, in cases where light emitted from the display element passes through the substrate, such as in transparent displays, bottom-emitting organic ELs, and liquid crystal displays, or when sensors and camera modules are placed on the back of the substrate to make smartphones and the like full-screen displays (notchless), the optical properties (more specifically, transparency, etc.) of the substrate are becoming increasingly important.

[0005] Given this background, there is a need for materials that have heat resistance comparable to existing aromatic polyimides, as well as reduced coloring and excellent transparency.

[0006] To reduce the coloration of polyimide, techniques are known to use aliphatic monomers to suppress the formation of CT complexes (Patent Documents 1 and 2), techniques to improve transparency by using monomers with fluorine atoms (Patent Document 3), and techniques to improve transparency by introducing sulfonium structures (Patent Document 4).

[0007] The polyimides described in Patent Documents 1 and 2 have high transparency and low coefficient of linear expansion (CTE), but due to their aliphatic structure, they have low thermal decomposition temperatures, making them difficult to apply to high-temperature processes used in the formation of electronic components. Furthermore, the polyimide described in Patent Document 3 has high transparency due to the presence of fluorine atoms, but its heat resistance still has room for improvement.

[0008] Prior art literature

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2016-29177

[0011] Patent Document 2: Japanese Patent Application Publication No. 2012-41530

[0012] Patent Document 3: Japanese Patent Application Publication No. 2014-70139

[0013] Patent Document 4: Japanese Patent Publication No. 2021-521284 Summary of the Invention

[0014] The problem the invention aims to solve

[0015] Furthermore, according to the technology described in Patent Document 4, polyimides with excellent transparency can be obtained. However, according to the research of the inventors, if the polyamic acid composition described in Patent Document 4 is coated onto a support and the polyamic acid is imidized, the internal stress at the interface between the resulting polyimide film and the support tends to increase. Hereinafter, the internal stress at the interface between the polyimide film and the support will sometimes be referred to simply as "internal stress." When the internal stress increases, it may be difficult to apply it to electronic devices. It is difficult to obtain a polyimide film that can improve transparency and reduce internal stress using only the technology described in Patent Documents 1 to 4.

[0016] This invention was made in view of the above-mentioned circumstances, and its object is to provide a polyimide film capable of improving transparency and reducing internal stress, as well as a polyimide precursor composition as a precursor thereto. Furthermore, it aims to provide products or components manufactured using the polyimide film and the polyimide precursor composition that require heat resistance and transparency. In particular, it aims to provide products or components on which the polyimide film of this invention is formed on the surface of inorganic materials such as glass, metal, metal oxides, and monocrystalline silicon.

[0017] Solutions for solving problems

[0018] <Methods of the Invention>

[0019] The present invention includes the following methods.

[0020] [1] A polyimide precursor composition comprising a polyimide precursor and an organic solvent.

[0021] The polyimide precursor has structural units represented by the following general formula (1) and the following general formula (2).

[0022] The content of the structural units represented by the following general formula (2) is 10 mol% or more and 100 mol% or less relative to the total amount of structural units in the polyimide precursor.

[0023]

[0024] In the general formulas (1) and (2), X comprises one or more groups selected from the group consisting of a tetravalent organic group represented by chemical formula (3) and a tetravalent organic group represented by chemical formula (4), and Y comprises one or more groups selected from the group consisting of a divalent organic group represented by chemical formula (5) and a divalent organic group represented by chemical formula (6).

[0025]

[0026] [2] According to the polyimide precursor composition described above [1], wherein, relative to the total amount of diamine residues in the polyimide precursor, the content of one or more residues selected from the group consisting of the divalent organic groups represented by the chemical formula (5) and the divalent organic groups represented by the chemical formula (6) is 50 mol% or more and 100 mol% or less.

[0027] [3] According to the polyimide precursor composition described in [1] or [2] above, wherein X in general formulas (1) and (2) further comprises one or more of the group consisting of a tetravalent organic group represented by the following chemical formula (7), a tetravalent organic group represented by the following chemical formula (8), a tetravalent organic group represented by the following chemical formula (9), a tetravalent organic group represented by the following chemical formula (10), and a tetravalent organic group represented by the following chemical formula (11).

[0028]

[0029] [4] According to the polyimide precursor composition described above [3], wherein, relative to the total amount of tetracarboxylic acid dianhydride residues in the polyimide precursor, the content of one or more residues selected from the group consisting of the tetravalent organic group represented by chemical formula (7), the tetravalent organic group represented by chemical formula (8), the tetravalent organic group represented by chemical formula (9), the tetravalent organic group represented by chemical formula (10) and the tetravalent organic group represented by chemical formula (11) is 5 mol% or more and 95 mol% or less.

[0030] [5] The polyimide precursor composition according to any one of [1] to [4] above, wherein the organic solvent is one or more selected from the group consisting of N-methyl-2-pyrrolidone, 1-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, N,N-dimethylpropionamide, N,N-diethylformamide and 1,3-dimethyl-2-imidazolinone.

[0031] [6] A polyimide film comprising a polyimide polyimide film having structural units shown in the following general formula (2),

[0032] The coefficient of linear expansion of the polyimide film is below 30 ppm / K.

[0033]

[0034] In the general formula (2), X comprises one or more groups selected from the group consisting of tetravalent organic groups represented by chemical formula (3) and tetravalent organic groups represented by chemical formula (4), and Y comprises one or more groups selected from the group consisting of divalent organic groups represented by chemical formula (5) and divalent organic groups represented by chemical formula (6).

[0035]

[0036] [7] According to the polyimide film described above [6], wherein, relative to the total amount of diamine residues in the polyimide, the content of one or more residues selected from the group consisting of divalent organic groups represented by chemical formula (5) and divalent organic groups represented by chemical formula (6) is 50 mol% or more and 100 mol% or less.

[0037] In the general formula (2), X further comprises: one or more of the following groups: a tetravalent organic group represented by the following chemical formula (7), a tetravalent organic group represented by the following chemical formula (8), a tetravalent organic group represented by the following chemical formula (9), a tetravalent organic group represented by the following chemical formula (10), and a tetravalent organic group represented by the following chemical formula (11).

[0038] The content of one or more residues selected from the group consisting of the tetravalent organic group shown in chemical formula (7), the tetravalent organic group shown in chemical formula (8), the tetravalent organic group shown in chemical formula (9), the tetravalent organic group shown in chemical formula (10), and the tetravalent organic group shown in chemical formula (11) is 5 mol% or more and 95 mol% or less, relative to the total amount of tetracarboxylic dianhydride residues in the polyimide.

[0039]

[0040] [8] The polyimide film according to [6] or [7] above, wherein the haze is less than 1.0%.

[0041] [9] A laminate having a support and a polyimide film as described in any one of [6] to [8].

[0042]

[10] An electronic device having a polyimide film as described in any one of [6] to [8] above and electronic components disposed on the polyimide film.

[0043]

[11] An electronic device having the aforementioned [9] laminate and electronic components disposed on the polyimide film of the laminate.

[0044]

[12] A method for manufacturing a laminate, the laminate having a support and a polyimide film.

[0045] The manufacturing method includes the following steps:

[0046] Step Sa involves forming a coating film containing the polyimide precursor by coating the polyimide precursor composition described in any one of [1] to [5] above onto a support; and

[0047] In step Sb, a polyimide film is formed on the support by heating the coating film obtained in step Sa.

[0048]

[13] A method for manufacturing a polyimide film, wherein a laminate having a support and a polyimide film is formed by the method described above

[12] , and the polyimide film is peeled off from the support.

[0049]

[14] A method for manufacturing an electronic device, wherein a laminate having a support and a polyimide film is formed by the method described above

[12] , and electronic components are formed on the polyimide film.

[0050] The effects of the invention

[0051] Polyimide films manufactured using the polyimide precursor composition of the present invention can improve transparency and reduce internal stress. Therefore, polyimide films manufactured using the polyimide precursor composition of the present invention are suitable as materials for electronic devices requiring transparency and reduced internal stress. Detailed Implementation

[0052] The following describes in detail suitable embodiments of the present invention, but the present invention is not limited to these embodiments. Furthermore, all academic and patent documents described in this specification are incorporated herein by reference.

[0053] First, the terms used in this specification will be explained. “Structural unit” refers to a repeating unit that constitutes a polymer. “Polyamic acid” is a polymer containing the structural unit shown in the following general formula (12) (hereinafter sometimes referred to as “structural unit (12)”) and having an imidization rate of 0 mol%. It should be noted that the method for determining the “imidization rate” is the same as or based on the method described in the examples below.

[0054]

[0055] In general formula (12), A 1 A represents a tetracarboxylic dianhydride residue (a tetravalent organic group derived from tetracarboxylic dianhydride). 2 It represents a diamine residue (a divalent organic group derived from a diamine).

[0056] "Polyimide precursor" refers to a polymer having structural unit (12) and structural unit shown in the following general formula (13) (hereinafter sometimes referred to as "structural unit (13)"). Structural unit (13) is a structural unit formed by imidizing the amide group in structural unit (12). Therefore, A in general formula (13) 1 A in general formula (12) 1 The meanings are the same, A in general formula (13) 2 A in general formula (12) 2 The meaning is the same. However, in this specification, a composition comprising a polymer (a polymer in which all structural unit (12) is imidized) with an imidization rate of 100 mol% and an organic solvent is also described as a "polyimide precursor composition".

[0057]

[0058] The total content of structural units (12) and structural units (13) relative to the total amount of structural units in the polyimide precursor (100 mol%) is preferably 80 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less, even more preferably 95 mol% or more and 100 mol% or less, and may also be 100 mol%.

[0059] Unless otherwise specified, the "coefficient of linear expansion" refers to the coefficient of linear expansion when the temperature drops from 100℃ to 400℃.

[0060] Hereinafter, the term "system" is sometimes added after the compound name to refer to compounds and their derivatives in an inclusive manner. When "system" is added after the compound name to indicate the polymer name, it means that the repeating unit of the polymer originates from the compound or its derivatives. Additionally, tetracarboxylic dianhydride is sometimes referred to as "acid dianhydride". Furthermore, unless otherwise specified, the components, functional groups, etc., exemplified in this specification may be used alone or in combination of two or more.

[0061] <Suitable Embodiments of the Invention>

[0062] The polyimide precursor composition according to this embodiment includes a polyimide precursor and an organic solvent. The polyimide precursor has structural units shown in general formula (1) and general formula (2). Hereinafter, the structural unit shown in general formula (1) is sometimes referred to as "structural unit (1)". In addition, the structural unit shown in general formula (2) is sometimes referred to as "structural unit (2)".

[0063]

[0064] In general formulas (1) and (2), X comprises one or more of the group consisting of a tetravalent organic group represented by chemical formula (3) and a tetravalent organic group represented by chemical formula (4), and Y comprises one or more of the group consisting of a divalent organic group represented by chemical formula (5) and a divalent organic group represented by chemical formula (6).

[0065]

[0066] Furthermore, in the polyimide precursor composition according to this embodiment, the content of structural unit (2) is 10 mol% or more and 100 mol% or less relative to the total amount of structural units (100 mol%) in the polyimide precursor. Hereinafter, the polyimide precursor contained in the polyimide precursor composition according to this embodiment will sometimes be referred to as "specific polyimide precursor". In addition, the content of structural unit (2) in the polyimide precursor relative to the total amount of structural units (100 mol%) will sometimes be referred to as "imidization rate".

[0067] Polyimide films manufactured using the polyimide precursor composition described in this embodiment can improve transparency and reduce internal stress. The reasons for this are speculated as follows.

[0068] In the polyimide precursor composition of this embodiment, the transparency is improved when a polyimide film is formed because a specific zeolite structure is introduced into a specific polyimide precursor.

[0069] On the other hand, as described above, if the polyamic acid with a saxon structure described in Patent Document 4 is used, there is a tendency for the internal stress to become larger. In contrast, the inventors have found that the solubility of a specific polyimide precursor formed by imidizing part or all of the polyamic acid containing a specific saxon structure is specifically improved in organic solvents; and that the internal stress can be reduced by using the specific polyimide precursor. The saxon structure having a tetravalent organic group as shown in chemical formulas (3) and (4) has a hexafluoroisopropylidene group or a fluorene group in the side chain. Therefore, it is believed that if the specific saxon structure is present in the polymer chain, the solubility is improved and gelation can be suppressed. In addition, it is believed that if the saxon structure having a tetravalent organic group as shown in chemical formula (3) or (4) is present in the polymer chain, the linearity is increased, and the orientation of the polymer chain is dramatically induced during imidization. As a result, the CTE is reduced and the internal stress is reduced. Therefore, the polyimide film manufactured using the polyimide precursor composition according to this embodiment can reduce the internal stress.

[0070] In this embodiment, in order to further reduce internal stress, the imidization rate is preferably 20 mol% or more, more preferably 30 mol% or more, even more preferably 40 mol% or more, and even more preferably 50 mol% or more. It may also be 60 mol% or more, 70 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, or 95 mol% or more.

[0071] In this embodiment, the specific polyimide precursor comprises one or more groups selected from the group consisting of divalent organic groups represented by chemical formula (5) and divalent organic groups represented by chemical formula (6) below. Since these organic groups have fluorine atoms, the aggregation of molecular chains is suppressed in this embodiment. Therefore, the polyimide precursor composition according to this embodiment can improve the solubility of the specific polyimide precursor in organic solvents, even if the imidization rate is 100 mol%.

[0072] The tetravalent organic group shown in formula (3) is a partial structure (residue) derived from 9,9-bis(trifluoromethyl)-2,3,6,7-xantontetracarboxylic dianhydride (hereinafter sometimes referred to as "6FCDA"). Additionally, the tetravalent organic group shown in formula (4) is a partial structure (residue) derived from spiro[11H-difurano[3,4-b:3',4'-i]xanton-11,9'-[9H]fluorene]-1,3,7,9-tetrone (hereinafter sometimes referred to as "SFDA"). Therefore, a particular polyimide precursor has one or more tetracarboxylic dianhydride residues selected from the group consisting of 6FCDA residues and SFDA residues.

[0073] In this embodiment, in order to further improve transparency, the content of one or more residues selected from the group consisting of 6FCDA residues and SFDA residues is preferably 5 mol% or more, more preferably 10 mol% or more, further preferably 20 mol% or more, even more preferably 30 mol% or more, and may also be 40 mol% or more or 50 mol% or more, relative to the total amount (100 mol%) of tetracarboxylic dianhydride residues in the specific polyimide precursor.

[0074] In a specific polyimide precursor, the content of one or more residues selected from the group consisting of 6FCDA residues and SFDA residues may be 100 mol% relative to the total amount (100 mol%) of tetracarboxylic dianhydride residues in the specific polyimide precursor. The specific polyimide precursor may also contain acid dianhydride residues other than 6FCDA residues and SFDA residues (other acid dianhydride residues). To further reduce internal stress, the content of one or more residues selected from the group consisting of 6FCDA residues and SFDA residues is preferably 95 mol% or less relative to the total amount of tetracarboxylic dianhydride residues in the specific polyimide precursor, more preferably 90 mol% or less, further preferably 80 mol% or less, even more preferably 70 mol% or less, and may also be 60 mol% or less.

[0075] To further improve transparency and reduce internal stress, the specific polyimide precursor preferably contains SFDA residues, and more preferably contains both 6FCDA residues and SFDA residues.

[0076] When synthesizing specific polyimide precursors, acid dianhydrides other than 6FCDA and SFDA can be used as monomers without compromising their properties. Examples of acid dianhydrides other than 6FCDA and SFDA include 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (hereinafter, sometimes referred to as "BPDA"), 4,4'-oxobisphthalic anhydride (hereinafter, sometimes referred to as "ODPA"), 4,4'-(hexafluoroisopropylidene)bisphthalic anhydride (hereinafter, sometimes referred to as "6FDA"), 2,3,3',4'-biphenyltetracarboxylic acid dianhydride (hereinafter, sometimes referred to as "a-BPDA"), 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (hereinafter, sometimes referred to as "BPAF"), pyromellitic dianhydride (hereinafter, sometimes referred to as "PMDA"), and 1,2,5,6-naphthalene. Tetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride (hereinafter, sometimes referred to as "NTCDA"), p-phenylenebis(triphenylene trihydride), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2'-oxodispiro[bicyclo[2.2.1]heptane-2,1'-cyclopentane-3',2”-bicyclo[2.2.1]heptane]-5,6:5”,6”-tetracarboxylic dianhydride and their derivatives, which may be used alone or in two or more forms.

[0077] Among them, PMDA, BPDA, and NTCDA have high linearity and are effective in reducing internal stress, while BPAF, 6FDA, and α-BPDA are effective in improving solubility. From the viewpoint of improving mechanical strength, ODPA is preferred. When a specific polyimide precursor contains NTCDA residues as other dianhydride residues, in order to further reduce internal stress, the content of NTCDA residues is preferably 5 mol% or more and 60 mol% or less relative to the total amount of tetracarboxylic acid dianhydride residues in the specific polyimide precursor, more preferably 10 mol% or more and 40 mol% or less.

[0078] In particular, to improve solubility in organic solvents by combining with one or more monomers selected from the group consisting of 6FCDA and SFDA, the dianhydride other than 6FCDA and SFDA is preferably selected from the group consisting of BPDA, ODPA, 6FDA, α-BPDA, and BPAF. That is, a particular polyimide precursor preferably contains one or more residues selected from the group consisting of BPDA residues, ODPA residues, 6FDA residues, α-BPDA residues, and BPAF residues as other dianhydride residues.

[0079] Furthermore, to further improve transparency and reduce internal stress, the content of one or more residues selected from the group consisting of BPDA residues, ODPA residues, 6FDA residues, α-BPDA residues, and BPAF residues is preferably 5 mol% or more and 95 mol% or less, more preferably 10 mol% or more and 95 mol% or less, more preferably 20 mol% or more and 90 mol% or less, even more preferably 30 mol% or more and 90 mol% or less, and may also be 40 mol% or more and 80 mol% or 40 mol% or more and 70 mol% or less, relative to the total amount of tetracarboxylic dianhydride residues in the specific polyimide precursor. Additionally, to further improve transparency and reduce internal stress, the specific polyimide precursor preferably includes one or more residues selected from the group consisting of BPDA residues, ODPA residues, and 6FDA residues as other acid dianhydride residues.

[0080] The BPDA residue is a tetravalent organic group as shown in chemical formula (7). The ODPA residue is a tetravalent organic group as shown in chemical formula (8). The 6FDA residue is a tetravalent organic group as shown in chemical formula (9). The α-BPDA residue is a tetravalent organic group as shown in chemical formula (10). The BPAF residue is a tetravalent organic group as shown in chemical formula (11).

[0081]

[0082] As described above, the specific polyimide precursor has one or more diamine residues selected from the group consisting of divalent organic groups represented by chemical formula (5) and divalent organic groups represented by chemical formula (6) as Y in structural units (1) and (2). The aforementioned specific diamine residues have high linearity, thus helping to reduce internal stress.

[0083] The divalent organic group shown in chemical formula (5) is a partial structure (residue) derived from 2,2'-bis(trifluoromethyl)benzidine (hereinafter sometimes referred to as "TFMB"). The divalent organic group shown in chemical formula (6) is a partial structure (residue) derived from 2,2'-bis(trifluoromethoxy)benzidine (hereinafter sometimes referred to as "TFMOB").

[0084] When synthesizing specific polyimide precursors, diamines other than TFMB and TFMOB can be used as monomers without compromising their properties. Examples of diamines other than TFMB and TFMOB include 9,9-bis(4-aminophenyl)fluorene (hereinafter, sometimes referred to as "BAFL"), 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether (hereinafter, sometimes referred to as "6FODA"), 4,4'-diaminodiphenyl sulfone (hereinafter, sometimes referred to as "DDS"), 4,4'-diaminobenzoylaniline (hereinafter, sometimes referred to as "DABA"), and 1,3-bis(3-aminopropyl)tetramethyldisiloxane (hereinafter, Sometimes referred to as "PAM-E"), m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, N,N'-bis(4-aminophenyl)terephthalamide, m-toluidine, o-toluidine, 4,4'-bis(4-aminophenoxy)biphenyl, 2-(4-aminophenyl)-6-aminobenzoxazole, 3,5-diaminobenzoic acid, 4,4'-diamino-3,3'-dihydroxybiphenyl, 4,4'-methylenebis(cyclohexylamine) and their derivatives, which may be used alone or in two or more forms.

[0085] Among them, BAFL, 6FODA and DDS can improve solubility, DABA is effective in reducing internal stress, and PAM-E can improve adhesion to the substrate.

[0086] To further improve transparency and further reduce internal stress, the content of one or more residues selected from the group consisting of TFMB residues and TFMOB residues is preferably 50 mol% or more and 100 mol% or less relative to the total amount (100 mol%) of diamine residues in the specific polyimide precursor, more preferably 60 mol% or more and 100 mol% or less, further preferably 70 mol% or more and 100 mol% or less, even more preferably 80 mol% or more and 100 mol% or less, and particularly preferably 90 mol% or more and 100 mol% or less.

[0087] To further improve transparency and further reduce internal stress, the specific polyimide precursor preferably satisfies condition 1 below, and more preferably satisfies condition 2 below.

[0088] Condition 1: The imidization rate is 50 mol% or more and 100 mol% or less.

[0089] Condition 2: It meets the above condition 1 and has SFDA residues as acid dianhydride residues.

[0090] Specific polyimide precursors are obtained, for example, by partially imidizing a polyamic acid (hereinafter, sometimes referred to as "polyamic acid (1)") with a specific structure. Polyamic acid (1) can be synthesized using known conventional methods, for example by reacting a diamine with a tetracarboxylic acid dianhydride in an organic solvent. An example of a specific method for synthesizing polyamic acid (1) will be described. First, a diamine solution is prepared by dissolving or dispersing the diamine in an organic solvent into a slurry under an inert gas atmosphere such as argon or nitrogen. Then, the tetracarboxylic acid dianhydride, either dissolved or dispersed in an organic solvent into a slurry or in a solid state, is added to the diamine solution.

[0091] When polyamic acid (1) is synthesized using diamine and tetracarboxylic dianhydride, the desired polyamic acid (1) (a polymer of diamine and tetracarboxylic dianhydride) can be obtained by adjusting the amount of diamine (in the case of multiple diamines, the amount of each diamine) and the amount of tetracarboxylic dianhydride (in the case of multiple tetracarboxylic dianhydrides, the amount of each tetracarboxylic dianhydride). The molar fraction of each residue in polyamic acid (1) is, for example, consistent with the molar fraction of each monomer (diamine and tetracarboxylic dianhydride) used in the synthesis of polyamic acid (1). Alternatively, polyamic acid (1) containing multiple tetracarboxylic dianhydride residues and multiple diamine residues can also be obtained by blending the two polyamic acids. The temperature conditions for the reaction of diamine and tetracarboxylic dianhydride, i.e., the synthesis reaction of polyamic acid (1), are not particularly limited, but are, for example, in the range of 20°C or higher and 150°C or lower. The reaction time for the synthesis reaction of polyamic acid (1) is, for example, in the range of 10 minutes or higher and 30 hours or lower.

[0092] The organic solvent used in the synthesis of polyamic acid (1) is preferably a solvent capable of dissolving the tetracarboxylic acid dianhydride and diamine used, and more preferably a solvent capable of dissolving the polyamic acid (1) produced. Examples of organic solvents used in the synthesis of polyamic acid (1) include urea solvents such as tetramethylurea and N,N-dimethylethylurea; sulfoxide solvents such as dimethyl sulfoxide; sulfone solvents such as diphenyl sulfone and tetramethyl sulfone; N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 1-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide (MPA), 3-butoxy-N, Amide solvents such as N-dimethylpropionamide, N,N-dimethylpropionamide, N,N-diethylformamide, 1,3-dimethyl-2-imidazolinone, and hexamethylphosphotriamide; ester solvents such as γ-butyrolactone; haloalkane solvents such as chloroform and dichloromethane; aromatic hydrocarbon solvents such as benzene and toluene; phenol solvents such as phenol and cresol; ketone solvents such as cyclopentanone; and ether solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and p-cresol methyl ether. These solvents are usually used alone, but two or more can be used in combination as needed. To improve the solubility and reactivity of polyamic acid (1), the organic solvent used in the synthesis reaction of polyamic acid (1) is preferably one or more solvents selected from the group consisting of amide solvents, ketone solvents, ester solvents, and ether solvents. Amide solvents are more preferred, and solvents selected from the group consisting of NMP, MPA, 1-butyl-2-pyrrolidone, 3-butoxy-N,N-dimethylpropionamide, N,N-dimethylpropionamide, N,N-diethylformamide, and 1,3-dimethyl-2-imidazolinone are even more preferred. Furthermore, the synthesis reaction of polyamic acid (1) is preferably carried out under an inert gas atmosphere such as argon or nitrogen.

[0093] The polyimide precursor composition according to this embodiment comprises a specific polyimide precursor and an organic solvent. To improve the solubility of the specific polyimide precursor, the organic solvent is preferably one of the solvents listed above used in the synthesis reaction of the polyamic acid (1). Specifically, the organic solvent in the polyimide precursor composition according to this embodiment is preferably one or more solvents selected from the group consisting of amide solvents, ketone solvents, ester solvents, and ether solvents; more preferably, an amide solvent; and even more preferably, one or more solvents selected from the group consisting of NMP, MPA, 1-butyl-2-pyrrolidone, 3-butoxy-N,N-dimethylpropionamide, N,N-dimethylpropionamide, N,N-diethylformamide, and 1,3-dimethyl-2-imidazolinone. It should be noted that the content of a specific polyimide precursor in the polyimide precursor composition involved in this embodiment is not particularly limited. Relative to the total amount of the polyimide precursor composition, it is, for example, more than 1% by weight and less than 80% by weight, preferably more than 5% by weight and less than 50% by weight, and more preferably more than 5% by weight and less than 30% by weight.

[0094] The polyimide precursor composition according to this embodiment can be prepared (partially imidized) from a solution (polyamic acid solution) containing polyamic acid (1) and an organic solvent. It should be noted that, hereinafter, "partially imidized" means imidizing polyamic acid (1) within the above-specified range (10 mol% or more and 100 mol% or less). Examples of organic solvents contained in the polyamic acid solution include those that can be used in the synthesis reaction of the polyamic acid (1). When obtaining polyamic acid (1) by the above method, the reaction solution (the solution after the reaction) itself can also be used as the polyamic acid solution for preparing the polyimide precursor composition. Alternatively, a polyamic acid solution can be prepared by dissolving solid polyamic acid (1) obtained by removing the solvent from the reaction solution in an organic solvent.

[0095] Typically, polyamic acid undergoes hydrolysis due to factors such as moisture, and its viscosity changes as its molecular weight decreases. Therefore, polyamic acid solutions are ideally stored at around -20°C. In contrast, the polyimide precursor composition of this embodiment is less susceptible to hydrolysis because some or all of the polyamic acid (1) is imidized, and it can be stored stably even at room temperature. Therefore, the polyimide precursor composition of this embodiment can reduce storage and transportation costs.

[0096] There are no particular limitations on the method for partially imidizing polyamic acid (1), and known methods can be used. Specific methods for partial imidization include thermal methods, chemical methods, and the use of pre-imidized raw materials to obtain a partially imidized specific polyimide precursor. From the viewpoint of controlling the imidization rate within the aforementioned specified range, the method of partial imidization using a chemical method (chemical imidization) is preferred. Tertiary amines and other byproducts generated by chemical imidization can be directly used for film formation while remaining in the polyimide precursor composition, or the specific polyimide precursor can be precipitated in a poor solvent to separate the byproducts, and then dissolved again in an organic solvent to obtain the polyimide precursor composition.

[0097] As a chemical imidization method, for example, a method can be described by adding one or more catalysts selected from the group consisting of imidizing catalyst and dehydration catalyst to a polyamic acid solution containing polyamic acid (1) to partially imidize the polyamic acid (1). The temperature conditions for the partial imidization of polyamic acid (1) are, for example, in the range of 20°C or higher and 150°C or lower. The reaction time for the partial imidization of polyamic acid (1) is, for example, in the range of 10 minutes or higher and 30 hours or lower. The imidization rate can be adjusted, for example, by changing at least one of the amount of imidizing catalyst, the amount of dehydration catalyst, the temperature conditions for partial imidization, and the reaction time for partial imidization.

[0098] As the imidization catalyst described above, there are no particular limitations, and tertiary amines can be used. Heterocyclic tertiary amines are preferred. Specific examples of preferred heterocyclic tertiary amines include pyridine, methylpyridine, dimethylpyridine, ethylpyridine, diethylpyridine, isoquinoline, and 1,2-dimethylimidazole. As the dehydration catalyst described above, there are no particular limitations, and acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, and trifluoroacetic anhydride are preferred examples.

[0099] The amount of imidization catalyst added is preferably 0.5 molar equivalents or more and 5.0 molar equivalents or less relative to the amide groups of polyamic acid (1), more preferably 0.5 molar equivalents or more and 2.5 molar equivalents or less, and even more preferably 0.6 molar equivalents or more and 2.0 molar equivalents or less. The amount of dehydration catalyst added is preferably 0.5 molar equivalents or more and 10.0 molar equivalents or less relative to the amide groups of polyamic acid (1), more preferably 0.5 molar equivalents or more and 5.0 molar equivalents or less, and even more preferably 0.6 molar equivalents or more and 3.0 molar equivalents or less. When adding the imidization catalyst and / or dehydration catalyst to the polyamic acid solution, it can be added directly if it is insoluble in an organic solvent, or it can be added to a solution dissolved in an organic solvent. In the method of adding directly if it is insoluble in an organic solvent, sometimes the reaction proceeds rapidly before the imidization catalyst and / or dehydration catalyst diffuse, resulting in the formation of a gel. Therefore, it is more preferable to mix the solution obtained by dissolving the imidization catalyst and / or dehydration catalyst in an organic solvent into the polyamic acid solution.

[0100] The weight-average molecular weight of a specific polyimide precursor depends on its application, but is preferably in the range of 10,000 to 1,000,000, more preferably in the range of 20,000 to 500,000, and even more preferably in the range of 30,000 to 200,000. If the weight-average molecular weight is 10,000 or higher, the viscosity of the polyimide precursor composition can be easily adjusted to a range suitable for coating (e.g., 0.5 Pa·s or higher and 10 Pa·s or lower). On the other hand, when the weight-average molecular weight is 1,000,000 or lower, it exhibits sufficient solubility in solvents, thus a coating film or polyimide film with a smooth surface and uniform thickness can be obtained using the polyimide precursor composition. The weight-average molecular weight used here refers to the polyethylene oxide equivalent value determined using gel permeation chromatography (GPC).

[0101] In addition, methods for controlling the molecular weight of a specific polyimide precursor include using an excess of either the acid dianhydride or the diamine, and quenching the reaction by reacting with monofunctional acid anhydrides or amines such as phthalic anhydride or aniline. When polymerization is carried out with an excess of either the acid dianhydride or the diamine, a polyimide film with sufficient strength can be obtained if their molar ratio is between 0.95 and 1.05. It should be noted that the above molar ratio is the ratio of the total mass of the diamine used in the synthesis of the specific polyimide precursor to the total mass of the acid dianhydride used in the synthesis of the specific polyimide precursor (total mass of diamine / total mass of acid dianhydride). Furthermore, by using end-capping with phthalic anhydride, maleic anhydride, aniline, etc., the coloring of the polyimide obtained using the specific polyimide precursor can be further reduced.

[0102] In the polyimide precursor composition described in this embodiment, various organic or inorganic low-molecular-weight compounds or high-molecular-weight compounds can be blended as additives. Examples of additives include plasticizers, antioxidants, dyes, surfactants, leveling agents, silicones, microparticles, and sensitizers. The microparticles include organic microparticles formed from polystyrene, polytetrafluoroethylene, etc., and inorganic microparticles formed from colloidal silica, carbon, layered silicates, etc., which can have porous or hollow structures. Furthermore, the function and morphology of the microparticles are not particularly limited; for example, they can be pigments, fillers, or fibrous particles.

[0103] In addition, to exhibit suitable adhesion to the support, the polyimide precursor composition according to this embodiment may contain a silane coupling agent. Known silane coupling agents may be used without particular limitation, but from the viewpoint of reactivity with a specific polyimide precursor, compounds containing amino groups are particularly preferred.

[0104] The mixing ratio of the silane coupling agent relative to 100 parts by weight of a specific polyimide precursor is preferably 0.01 parts by weight or more and 0.50 parts by weight or less, more preferably 0.01 parts by weight or more and 0.10 parts by weight or less, and even more preferably 0.01 parts by weight or more and 0.05 parts by weight or less. By setting the mixing ratio of the silane coupling agent to 0.01 parts by weight or more, the peeling inhibition effect on the support can be fully utilized. By setting the mixing ratio of the silane coupling agent to 0.50 parts by weight or less, the molecular weight reduction of the specific polyimide precursor can be suppressed, thus suppressing the embrittlement of the polyimide film.

[0105] The polyimide film according to this embodiment is obtained by imidizing (fully imidizing) a specific polyimide precursor in the polyimide precursor composition according to this embodiment. Therefore, the polyimide film according to this embodiment is a polyimide film containing a polyimide having a structural unit (2). In addition, the preferred configuration of the structural unit (2) (the type of each residue, the content of each residue, etc.) is the same as the preferred configuration of the structural unit (2) in the specific polyimide precursor described above. The polyimide film according to this embodiment can be obtained by known methods, and its manufacturing method is not particularly limited. Hereinafter, an example of a method for obtaining the polyimide film according to this embodiment by imidizing a specific polyimide precursor will be described. Imidization is performed by dehydrating and ring-closing the specific polyimide precursor. This dehydration and ring closure can be performed by an azeotropic method using an azeotropic solvent, a thermal method, or a chemical method.

[0106] The dehydration and ring-closing of a specific polyimide precursor can be achieved by heating the specific polyimide precursor. There are no particular limitations on the method of heating the specific polyimide precursor; for example, after coating the polyimide precursor composition according to this embodiment onto a support such as a glass substrate, metal plate, or PET film (polyethylene terephthalate film), heat treatment of the specific polyimide precursor can be performed at a temperature between 40°C and 500°C. According to this method, a laminate according to this embodiment, having a support and a polyimide film disposed on the support (more specifically, a polyimide film containing an imide derivative of the specific polyimide precursor), can be obtained. It should be noted that the heating time for imidization varies depending on the amount of specific polyimide precursor being processed for dehydration and ring-closing, and the heating temperature, but is generally preferably set to a range of 1 minute to 300 minutes after the processing temperature reaches its maximum. It should be noted that when using a specific polyimide precursor with an imidization rate of 100 mol% to form a polyimide film, the solvent is removed by heating the polyimide precursor composition to thin the specific polyimide precursor.

[0107] The polyimide film involved in this embodiment is obtained using the polyimide precursor composition involved in this embodiment, and therefore is a polyimide film with high transparency and low CTE. The CTE of the polyimide film involved in this embodiment is preferably 30 ppm / K or less, more preferably 25 ppm / K or less, further preferably 20 ppm / K or less, and even more preferably 15 ppm / K or less. The method for measuring CTE is the same as or based on the methods described in the examples below. It should be noted that the lower limit of the CTE of the polyimide film involved in this embodiment is not particularly limited, for example, it is 1 ppm / K or more.

[0108] The polyimide film according to this embodiment (more specifically, a polyimide film containing an imide compound of a specific polyimide precursor) is colorless, transparent, and has low yellowness. It possesses a glass transition temperature (heat resistance) capable of withstanding the fabrication process of thin-film transistors (TFTs), making it suitable as a transparent substrate material for flexible displays. The content of polyimide (more specifically, an imide compound of a specific polyimide precursor) in the polyimide film according to this embodiment, relative to the total amount of the polyimide film, is, for example, 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and may also be 100% by weight. Other components in the polyimide film besides polyimide include, for example, the aforementioned additives (more specifically, microparticles, etc.).

[0109] The electronic device (more specifically, a flexible device, etc.) according to this embodiment has the polyimide film according to this embodiment and electronic components disposed directly or indirectly on the polyimide film. Alternatively, the electronic device (more specifically, a flexible device, etc.) according to this embodiment may be an electronic device having a laminate and electronic components, wherein the laminate has a support and a polyimide film (more specifically, a polyimide film containing an imide compound of a specific polyimide precursor), and the electronic components are disposed directly or indirectly on the polyimide film of the laminate. In manufacturing the electronic device according to this embodiment for a flexible display, firstly, an inorganic substrate such as glass is used as a support, and a polyimide film is formed on it. Then, by disposing (forming) electronic components such as TFTs on the polyimide film, the electronic device is formed on the support. The process of forming TFTs is usually carried out in a wide temperature range of 150°C to 650°C. However, in order to achieve the desired performance, oxide semiconductor layers and a-Si layers are formed at temperatures above 300°C. Depending on the situation, lasers or other methods are sometimes used to crystallize a-Si.

[0110] At this point, when the thermal decomposition temperature of the polyimide film is low, exhaust gas occurs during the formation of electronic components, which adheres to the oven in the form of sublimation, potentially causing oven contamination. Alternatively, it can lead to the peeling of inorganic films (such as barrier films described later) formed on the polyimide film and electronic components. Therefore, the 1% weight loss temperature of the polyimide is preferably 500°C or higher. A higher upper limit for the 1% weight loss temperature of the polyimide is preferable, for example, 600°C. The 1% weight loss temperature can be adjusted, for example, by changing the content of residues with rigid structures (more specifically, BPDA residues, etc.). More specifically, before TFT formation, inorganic films such as silicon oxide films (SiOx films) and silicon nitride films (SiNx films) are formed on the polyimide film as barrier films. At this point, if the heat resistance of the polyimide is low, if imidization is incomplete, or if there is a large amount of residual solvent, the polyimide may peel off from the inorganic film during high-temperature processes after the inorganic film is laminated due to volatile components such as decomposition gases from the polyimide. Therefore, based on the premise that the 1% weight loss temperature of polyimide is above 500°C, it is ideal to have a weight loss rate of less than 1% when polyimide is isothermally held in a temperature range of above 400°C and below 450°C.

[0111] Furthermore, if the glass transition temperature (Tg) of polyimide is significantly lower than the process temperature, positional shifts may occur during the formation of electronic components. Therefore, the Tg of polyimide is preferably 300°C or higher, more preferably 350°C or higher, even more preferably 400°C or higher, and even more preferably 420°C or higher. A higher upper limit for the Tg of polyimide is preferable, for example, 470°C. Additionally, generally, the coefficient of linear expansion (CTE) of the glass substrate is smaller than that of the resin, thus internal stress occurs between the glass substrate and the polyimide film. If the internal stress of the laminate containing the glass substrate used as a support, the electronic components, and the polyimide film is high, the laminate containing the polyimide film expands during the high-temperature TFT formation process and then contracts upon cooling to room temperature, causing problems such as warping and breakage of the glass substrate, and peeling of the polyimide film from the glass substrate. Therefore, in the laminate having a glass substrate (support) and a polyimide film (the laminate involved in this embodiment), the internal stress between the polyimide film and the glass substrate is preferably 40 MPa or less, more preferably 35 MPa or less, and even more preferably 28 MPa or less. The lower the lower limit of the internal stress, the better; it can be 0 MPa. The method for measuring the internal stress is the same as or based on the method described in the embodiments below.

[0112] The polyimide obtained from the polyimide precursor composition according to this embodiment can be suitably used as a material for display substrates such as TFT substrates and touch panel substrates. When using polyimide for the above-mentioned applications, the following method is generally employed: after forming electronic devices (more specifically, electronic devices on which electronic components are formed on the polyimide film) on the support as described above, the polyimide film is peeled off from the support. Furthermore, alkali-free glass is suitable as the material for the support. Hereinafter, an example of a method for manufacturing a laminate of the polyimide film and the support will be described in detail.

[0113] First, the polyimide precursor composition according to this embodiment is coated (cast) onto a support to form a laminate containing the coated film (step Sa), which is formed by a coated film containing a specific polyimide precursor and a support. Next, the laminate containing the coated film is heated, for example, at a temperature of 40°C or higher and 200°C or lower. The heating time at this time is, for example, 3 minutes or more and 120 minutes or less. It should be noted that a multi-stage heating process can be provided, such as heating the laminate containing the coated film at 50°C for 30 minutes, and then heating at 100°C for 30 minutes. Next, in order to promote the imidization of the specific polyimide precursor in the coated film, the laminate containing the coated film is heated, for example, at a maximum temperature of 200°C or higher and 500°C or lower (step Sb). The heating time at this time (heating time at the maximum temperature) is, for example, 1 minute or more and 300 minutes or less. At this time, it is preferable to gradually increase the temperature from a low temperature to the maximum temperature. The heating rate is preferably 2°C / min or more and 10°C / min or less, more preferably 4°C / min or more and 10°C / min or less. Furthermore, the maximum temperature is preferably in the range of 250°C or more and 450°C or less. If the maximum temperature is 250°C or more, imidization is sufficiently carried out; if the maximum temperature is 450°C or less, thermal degradation and coloration of the polyimide can be suppressed. Alternatively, the temperature can be maintained at any temperature for any time before reaching the maximum temperature. The imidization reaction can be carried out in air, under reduced pressure, or in a non-reactive gas such as nitrogen, but for higher transparency, it is preferable to carry it under reduced pressure or in a non-reactive gas such as nitrogen. Additionally, known devices such as hot air ovens, infrared ovens, vacuum ovens, inert ovens, and hot plates can be used as heating devices. Through these processes, the specific polyimide precursor in the coated film is imidized, and a laminate of a support and a polyimide film (a film containing an imidized version of the specific polyimide precursor) can be obtained (i.e., the laminate according to this embodiment).

[0114] The method for peeling the polyimide film from the resulting laminate of the support and the polyimide film can be any known method. For example, it can be peeled by hand, or by using mechanical devices such as drive rollers or robots. Alternatively, a method can be employed that involves: providing a release layer between the support and the polyimide film; forming a silicon oxide film on a substrate with multiple grooves; using the silicon oxide film as a base layer to form the polyimide film; and then wetting the space between the substrate and the silicon oxide film with an etching solution of silicon oxide, thereby peeling off the polyimide film. Another method can be used to separate the polyimide film by laser irradiation.

[0115] The transparency of the polyimide film can be evaluated using the total transmittance (TT) according to JIS K7361-1:1997 and the haze according to JIS K7136-2000. When using a polyimide film in applications requiring high transparency, the total transmittance of the polyimide film is preferably 75% or more, more preferably 80% or more. Furthermore, when using a polyimide film in applications requiring high transparency, the haze of the polyimide film is preferably 1.5% or less, more preferably 1.2% or less, further preferably 1.0% or less, and can also be 0%. In applications requiring high transparency, the polyimide film is required to have high transmittance across the entire wavelength range; however, polyimide films tend to absorb light from shorter wavelengths, and the film itself is mostly colored yellow. To use a polyimide film in applications requiring high transparency, it is preferable to reduce the coloration of the polyimide film. Specifically, for the use of polyimide films in applications requiring high transparency, the yellowness (YI) of the polyimide film is preferably 25 or less, more preferably 20 or less, and can also be 0. YI can be measured according to JIS K7373-2006. Thus, the polyimide film, with reduced coloration and imparted transparency, is suitable for use as a transparent substrate in applications such as replacing glass; substrates with sensors or camera modules mounted on their back sides.

[0116] Furthermore, in applications requiring transparency, high transmittance of blue light (light with a wavelength around 470 nm) is particularly desirable from the viewpoint of color reproduction, and practically, high transmittance at a wavelength of 400 nm (hereinafter sometimes referred to as "400 nm transmittance") is required. From the viewpoint of color reproduction, the 400 nm transmittance of the polyimide film is preferably 40% or more, more preferably 50% or more, further preferably 55% or more, and even more preferably 60% or more. There is no particular upper limit to the 400 nm transmittance of the polyimide film, and it can be 100%.

[0117] Furthermore, flexible displays employ two light extraction methods: top emission, which extracts light from the surface of the TFT, and bottom emission, which extracts light from the back of the TFT. In the top emission method, since the light is not blocked by the TFT, it is easier to increase the aperture ratio and achieve high-resolution image quality. The bottom emission method is easier to manufacture because it facilitates the alignment of the TFT and pixel electrodes. If the TFT is transparent, the aperture ratio can be increased even in the bottom emission method; therefore, there is a tendency to use the easier-to-manufacture bottom emission method in large displays. The polyimide film involved in this embodiment has low YI and excellent heat resistance, therefore it can be applied to either of the aforementioned light extraction methods.

[0118] Furthermore, in intermittent device fabrication processes such as coating a polyimide precursor composition onto a support like a glass substrate, heating to imidize it, forming electronic components, and then peeling off the polyimide film, excellent adhesion between the support and the polyimide film is preferable. Here, adhesion refers to adhesion strength. In fabrication processes where electronic components are formed on the polyimide film on the support, and then the polyimide film with the electronic components is peeled off from the support, excellent adhesion between the polyimide film and the support allows for more accurate formation or mounting of the electronic components. In manufacturing processes where electronic components are placed on the support with the polyimide film in between, from the viewpoint of improving productivity, higher peel strength between the support and the polyimide film is better. Specifically, the peel strength is preferably 0.05 N / cm or more, more preferably 0.1 N / cm or more.

[0119] In the manufacturing process described above, the polyimide film is typically peeled from the laminate of the support and the polyimide film using laser irradiation. In this case, the polyimide film needs to absorb the laser, therefore the cutoff wavelength of the polyimide film must be longer than the wavelength of the laser used for peeling. In laser peeling, XeCl excimer lasers with a wavelength of 308 nm are mostly used; therefore, the cutoff wavelength of the polyimide film is preferably 312 nm or more, more preferably 330 nm or more. On the other hand, if the cutoff wavelength is too long, the polyimide film tends to be yellow; therefore, the cutoff wavelength of the polyimide film is preferably 390 nm or less. From the viewpoint of balancing transparency (low yellowing) and the processability of laser peeling, the cutoff wavelength of the polyimide film is preferably 320 nm or more and 390 nm or less, more preferably 330 nm or more and 380 nm or less. It should be noted that the cutoff wavelength in this specification refers to the wavelength at which the transmittance, as measured by a UV-Vis spectrophotometer, is below 0.1%.

[0120] The polyimide precursor composition described in this embodiment can be used directly in coating and molding processes for products and components, or as a material for further coating or other treatments on molded articles formed into films. For use in coating or molding processes, the polyimide precursor composition can be dissolved or dispersed in an organic solvent as needed, and then, as needed, light-curing components, thermosetting components, non-polymerizable adhesive resins, and other components can be blended to prepare a composition containing a specific polyimide precursor.

[0121] Various inorganic thin films, such as metal oxide films and transparent electrodes, can also be formed on the surface of the polyimide film involved in this embodiment. There are no particular limitations on the methods for forming these inorganic thin films; examples include sputtering, vacuum evaporation, ion plating, and other PVD and CVD methods.

[0122] In addition to its heat resistance, low thermal expansion, and transparency, the polyimide film described in this embodiment exhibits low internal stress when laminated with a glass substrate, ensuring excellent adhesion to inorganic materials during high-temperature processes. Therefore, it is preferably used in fields and products where these properties are effective. For example, the polyimide film described in this embodiment is preferably used in image display devices such as liquid crystal displays, organic EL displays, and electronic paper, as well as printed materials, color filters, flexible displays, optical films, 3D displays, touch panels, transparent conductive film substrates, and solar cells. More preferably, it is used as a replacement material for currently used glass components. In these applications, the thickness of the polyimide film is, for example, 1 μm or more and 200 μm or less, preferably 5 μm or more and 100 μm or less. The thickness of the polyimide film can be measured using a laser holographic measuring instrument.

[0123] Furthermore, the polyimide precursor composition according to this embodiment can be suitably used in a method for manufacturing a polyimide film, such as coating a polyimide precursor composition onto a support, heating to imidize it, and then peeling off the polyimide film from the support. Additionally, the polyimide precursor composition according to this embodiment can be suitably used in an intermittent device fabrication process, such as coating a polyimide precursor composition onto a support, heating to imidize it, forming electronic components or the like on the formed polyimide film, and then peeling off the polyimide film with the electronic components or the like from the support. Therefore, this embodiment also includes a method for manufacturing a polyimide film, wherein after obtaining a laminate using the laminate manufacturing method according to this embodiment, a polyimide film is obtained by peeling off the polyimide film from the support. Furthermore, this embodiment also includes a method for manufacturing an electronic device, wherein after obtaining a laminate using the laminate manufacturing method according to this embodiment, electronic components are formed on the formed polyimide film.

[0124] Example

[0125] The following describes embodiments of the present invention, but the scope of the present invention is not limited to the following embodiments.

[0126] <Methods for Determining Physical Properties>

[0127] First, the method for determining the physical properties of polyimide (polyimide film) will be explained.

[0128] [Yellowness (YI)]

[0129] For the polyimide films in each laminate obtained in the examples and comparative examples described later, the transmittance at wavelengths of 200 nm and above and 800 nm and below was measured using a UV-Vis-NIR spectrophotometer (V-650 manufactured by Japan Spectrophotometer Co., Ltd.), and the yellowness (YI) of the polyimide film was calculated according to the formula described in JIS K7373-2006.

[0130] [400nm transmittance]

[0131] For the polyimide films in each laminate obtained in the examples and comparative examples described later, the transmittance (400nm transmittance) at a wavelength of 400nm was measured using a UV-Vis-NIR spectrophotometer (Nippon Spectrophotometer, "V-650").

[0132] [Haze]

[0133] For the polyimide films peeled from each laminate obtained from the examples and comparative examples described later, the haze was measured using an integrating sphere haze meter (Murakami Color Technology Research Institute Co., Ltd. "HM-150N") according to the method described in JIS K7136-2000. When the haze was 1.0% or less, it was evaluated as "excellent transparency". On the other hand, when the haze exceeded 1.0%, it was evaluated as "non-excellent transparency".

[0134] [Internal Stress]

[0135] On a Corning glass substrate (material: alkali-free glass, thickness: 0.7 mm, size: 100 mm × 100 mm) with pre-measured warpage, the polyimide precursor compositions prepared in the examples described later or the polyamic acid solutions prepared in the comparative examples described later were coated using a spin coater. The substrate was heated at 120°C for 30 minutes in air, followed by heating at 430°C for 30 minutes in a nitrogen atmosphere to obtain a laminate with a polyimide film of 10 μm thickness on the glass substrate. To eliminate the influence of water absorption by the polyimide film, the laminate was dried at 120°C for 10 minutes, and the warpage of the laminate in a nitrogen atmosphere at 25°C was measured using a thin film stress measuring device (KLA Corporation, "FLX-2320-S"). Then, based on the warpage of the glass substrate and the laminate before polyimide film formation, the internal stress generated between the glass substrate and the polyimide film was calculated using the Stoney formula. When the internal stress is below 28 MPa, it is evaluated as "internal stress can be reduced". On the other hand, when the internal stress exceeds 28 MPa, it is evaluated as "internal stress cannot be reduced".

[0136] [Internal stress reduction rate]

[0137] First, using the polyamic acid solutions prepared in the examples described later (the solutions used in the preparation of each polyimide precursor composition), the internal stress was measured using the method described in the [Internal Stress] section above. Hereinafter, the internal stress value obtained here will be referred to as "Internal Stress before partial imidization". Next, using the polyimide precursor compositions prepared in the examples described later, the internal stress was measured using the method described in the [Internal Stress] section above. Hereinafter, the internal stress value obtained here will be referred to as "Internal Stress after partial imidization". Then, the internal stress reduction rate (unit: %) was calculated according to the following formula.

[0138] Internal stress reduction rate = 100 × (1 - internal stress after partial imidization / internal stress before partial imidization)

[0139] It should be noted that the higher the internal stress reduction rate, the lower the internal stress compared to the case where partial imidization does not occur. The internal stress reduction rate is preferably 20% or more, more preferably 50% or more, and even more preferably 80% or more.

[0140] [Coefficient of linear expansion (CTE)]

[0141] For the polyimide films peeled from the laminates obtained from the examples and comparative examples described later, the CTE was measured using a thermal analysis apparatus (Hitachi High-Tech Corporation, "TMA / SS7100") under a load of 29.8 mN. Specifically, the CTE was determined based on the deformation of the polyimide film (3 mm wide and 10 mm long) at 10 °C / min from 20 °C to 450 °C in a nitrogen atmosphere, followed by cooling to 20 °C at 40 °C / min, and the deformation at 100 °C to 400 °C during the cooling process.

[0142] [Imidification rate]

[0143] First, the polyimide precursor compositions prepared in the examples described later, or the polyamic acid solutions prepared in the comparative examples described later, were coated onto a glass substrate. After heating at 120°C in air for 30 minutes, the substrate was then heated at 430°C in a nitrogen atmosphere for 30 minutes to obtain a polyimide film (thickness: 10 μm). Next, the infrared absorption spectra of each polyimide film were measured using a Fourier transform infrared spectrophotometer (FT / IR-6100, manufactured by Nippon Spectrophotometer Co., Ltd.) by total reflectance measurement (ATR method). Hereinafter, the infrared absorption spectra obtained here will be referred to as "IR". F ".

[0144] Next, the polyimide precursor compositions prepared in the examples described later or the polyamic acid solutions prepared in the comparative examples described later were coated onto a glass substrate and heated at 60°C in air for 60 minutes to obtain a thin film (thickness: 10 μm). Then, the infrared absorption spectra of each thin film were measured using a Fourier transform infrared spectrophotometer (FT / IR-6100, manufactured by Nippon Spectrophotometer Co., Ltd.) by total internal reflection measurement (ATR method). Hereinafter, the infrared absorption spectra obtained here will be referred to as "IR". V Then, the imidization rate (in mol%) is calculated using the formula shown below.

[0145] Imidification rate = 100 × (V) 1340 / V 1500 ) / (F 1340 / F 1500 )

[0146] V 1500 IR V 1500cm -1 Nearby peak intensity originating from aromatic rings

[0147] V 1340 IR V 1340cm -1 Nearby peak intensity derived from imide groups

[0148] F 1500 IR F 1500cm -1 Nearby peak intensity originating from aromatic rings

[0149] F 1340 IR F 1340cm -1 Nearby peak intensity derived from imide groups

[0150] <Preparation of polyamic acid solution>

[0151] The preparation methods of polyamic acid solutions P1 to P16 used in the examples and comparative examples will be described below. It should be noted that the compounds and reagents will be referred to by the following abbreviations. Furthermore, the preparation of polyamic acid solutions P1 to P16 was carried out under a nitrogen atmosphere.

[0152] NMP: N-methyl-2-pyrrolidone

[0153] MPA: 3-Methoxy-N,N-Dimethylpropionamide

[0154] BPDA: 3,3',4,4'-Biphenyltetracarboxylic acid dianhydride

[0155] NTCDA: 2,3,6,7-Naphthalenetetracarboxylic acid dianhydride

[0156] SFDA: Spiro[11H-difurano[3,4-b:3',4'-i]xanton-11,9'-[9H]fluorene]-1,3,7,9-tetraone

[0157] 6FCDA: 9,9-bis(trifluoromethyl)-2,3,6,7-xanthontetracarboxylic acid dianhydride

[0158] 6FDA: 4,4'-(hexafluoroisopropylidene)bisphthalic anhydride

[0159] PA: Phthalic anhydride

[0160] TFMB: 2,2'-bis(trifluoromethyl)benzidine

[0161] TFMOB: 2,2'-bis(trifluoromethoxy)benzidine

[0162] DMI: 1,2-Dimethylimidazole

[0163] AC2O: Acetic anhydride

[0164] [Preparation of polyamic acid solution P1]

[0165] In a 300 mL glass detachable flask equipped with a stirrer featuring a stainless steel stirring rod and a nitrogen inlet tube, 60.0 g of NMP was added as the organic solvent for polymerization. Next, while stirring the contents of the flask, 7.097 g of TFMB was added and dissolved. Then, 3.664 g of SFDA and 4.238 g of BPDA were added to the contents of the flask, and the mixture was stirred for 24 hours at 23°C to obtain a polyamic acid solution P1.

[0166] [Preparation of polyamic acid solution P2]

[0167] In a 300 mL glass detachable flask equipped with a stirrer featuring a stainless steel stirring rod and a nitrogen inlet tube, 60.0 g of MPA was added as the organic solvent for polymerization. Next, while stirring the contents of the flask, 7.097 g of TFMB was added and dissolved. Then, 3.664 g of SFDA and 4.238 g of BPDA were added to the contents of the flask, and the mixture was stirred for 24 hours at 23°C to obtain a polyamic acid solution P2.

[0168] [Preparation of polyamic acid solution P3]

[0169] In a 300 mL glass detachable flask equipped with a stirrer featuring a stainless steel stirring rod and a nitrogen inlet tube, 60.0 g of MPA was added as the organic solvent for polymerization. Next, while stirring the contents of the flask, 7.020 g of TFMB was added and dissolved. Then, 3.625 g of SFDA, 4.192 g of BPDA, and 0.162 g of PA were added to the contents of the flask. The mixture was stirred for 24 hours at 23°C to obtain a polyamic acid solution P3.

[0170] [Preparation of polyamic acid solutions P4-P16]

[0171] Except for the dianhydrides and their proportions used, and the diamines and their proportions used, as shown in Table 1, polyamic acid solutions P4 to P16 were prepared using the same method as for polyamic acid solution P1. It should be noted that the total mass of dianhydrides used in preparing polyamic acid solutions P4 to P16 is the same as that used in polyamic acid solution P1. Furthermore, the total mass of diamines used in preparing polyamic acid solutions P4 to P9 and P16 is the same as that used in polyamic acid solution P1. Additionally, the total mass of diamines used in preparing polyamic acid solutions P10 to P15 is 1.01 times the total mass of diamines used in preparing polyamic acid solution P1.

[0172] Table 1 shows the dianhydrides and their proportions used, the diamines and their proportions used, the amount of PA added, and the types of solvents used for polyamic acid solutions P1 to P16. It should be noted that in Table 1, "-" indicates that this component was not used. Furthermore, the values ​​in the "Dianhydrides" column of Table 1 represent the content of each dianhydride relative to the total amount of dianhydrides used (100 mol%) (in mol%). Similarly, the values ​​in the "Diamines" column represent the content of each diamine relative to the total amount of dianhydrides used (100 mol%) (in mol%). Finally, the values ​​in the "PA" column represent the amount of PA added relative to the total amount of dianhydrides used (100 mol%) (in mol%). Moreover, for polyamic acid solutions P1 to P16, the molar fractions of each residue of polyamic acid in the prepared polyamic acid solutions are consistent with the molar fractions of each monomer (diamine and dianhydride) used in the synthesis of polyamic acid.

[0173] [Table 1]

[0174]

[0175] <Fabrication of Polyimide Films (Laminates)>

[0176] The following describes the methods for preparing the polyimide films (laminates) of the examples and comparative examples. It should be noted that the preparation of the polyimide precursor compositions used in the examples was carried out under a nitrogen atmosphere.

[0177] [Example 1]

[0178] In a 300 mL glass detachable flask equipped with a stirrer featuring a stainless steel stirring rod and a nitrogen inlet tube, 75.0 g of polyamic acid solution P1 was added. Then, while stirring the contents of the flask, 75.0 g of NMP and DMI in an amount equal to 1.2 molar equivalents of the amide groups of the polyamic acid in solution P1 were added to the flask, and the mixture was stirred until homogeneous. Next, while stirring the contents of the flask, AC2O in an amount equal to 1.2 molar equivalents of the amide groups of the polyamic acid in solution P1 was added to the flask, and the mixture was stirred for 6 hours at 23°C to obtain a polyimide precursor composition. The obtained polyimide precursor composition was coated onto a glass substrate (made by Corning Incorporated, material: alkali-free glass, thickness: 0.7 mm, size: 100 mm × 100 mm) using a spin coater. The resulting coating film was heated at 80°C in air for 30 minutes, and then heated at 430°C in a nitrogen atmosphere for 30 minutes to obtain a laminate with a polyimide film of 10 μm thickness on the glass substrate (laminate of Example 1).

[0179] [Example 2]

[0180] The laminate of Example 2 was obtained by using 75.0 g of polyamic acid solution P2 instead of 75.0 g of polyamic acid solution P1, and 75.0 g of MPA instead of 75.0 g of NMP, except that the same method as in Example 1 was used.

[0181] [Example 3]

[0182] The laminate of Example 3 was obtained by using 75.0 g of polyamic acid solution P3 instead of 75.0 g of polyamic acid solution P1, and 75.0 g of MPA instead of 75.0 g of NMP, except that the same method as in Example 1 was used.

[0183] [Examples 4-7]

[0184] Except for the types of polyamic acid solutions used, as shown in Table 2, the laminates of Examples 4 to 7 were obtained using the same method as in Example 1.

[0185] [Examples 8 and 9]

[0186] The types of polyamic acid solutions used are shown in Table 2. The heating conditions for coating the film under nitrogen atmosphere were changed to "350°C for 60 minutes". Otherwise, the laminates of Examples 8 and 9 were obtained using the same method as in Example 1.

[0187] [Examples 10-16]

[0188] The types of polyamic acid solutions used are shown in Table 2, as are the amounts of DMI and AC2O added. The heating conditions for coating the film under nitrogen atmosphere were changed to "450°C for 30 minutes". Otherwise, the laminates of Examples 10 to 16 were obtained using the same method as in Example 1.

[0189] [Comparative Example 1]

[0190] The polyamic acid solution P1 was coated onto a glass substrate (made by Corning Incorporated, material: alkali-free glass, thickness: 0.7 mm, size: 100 mm × 100 mm) using a spin coater. After heating at 120°C in air for 30 minutes, it was heated at 430°C in a nitrogen atmosphere for 30 minutes to obtain a laminate with a polyimide film of 10 μm thickness on the glass substrate (laminate of Comparative Example 1).

[0191] [Comparative Examples 2-7]

[0192] Except for the types of polyamic acid solutions used, as shown in Table 3, laminates of Comparative Examples 2 to 7 were obtained using the same method as Comparative Example 1.

[0193] [Compare Examples 8 and 9]

[0194] The types of polyamic acid solutions used are shown in Table 3. The heating conditions for coating the film under nitrogen atmosphere were changed to "350°C for 60 minutes". Otherwise, the laminates of Comparative Examples 8 and 9 were obtained by using the same method as Comparative Example 1.

[0195] [Comparative Examples 10-15]

[0196] The types of polyamic acid solutions used are shown in Table 3. The heating conditions for coating the film under nitrogen atmosphere were changed to "450°C for 30 minutes". Otherwise, the laminates of Comparative Examples 10 to 15 were obtained using the same method as Comparative Example 1.

[0197] [Comparative Example 16]

[0198] In a 300 mL glass flask equipped with a stirrer featuring a stainless steel stirring rod and a nitrogen inlet tube, 75.0 g of polyamic acid solution P16 was added. Next, while stirring the contents of the flask, 75.0 g of NMP and 5.63 g of DMI were added, stirring until the contents became homogeneous. Then, while stirring the contents of the flask, 5.98 g of AC2O was added; the contents of the flask became non-flowing, and a gel precipitated in the flask.

[0199] Regarding Examples 1-16 and Comparative Examples 1-16, the types of polyamic acid solutions used, the amount of DMI used, the amount of AC2O used, the imidization rate, internal stress, internal stress reduction rate, CTE, YI, 400nm transmittance, and haze are shown in Tables 2 and 3. It should be noted that in Tables 2 and 3, the values ​​in the "DMI" and "AC2O" columns are all molar equivalent ratios relative to the amide groups of the polyamic acid (unit: times molar equivalents). Additionally, in Table 3, a "-" in the "DMI" and "AC2O" columns indicates that this component was not used. Furthermore, in Table 3, a "-" in the internal stress reduction rate and CTE columns indicates that they were not measured.

[0200] [Table 2]

[0201]

[0202] [Table 3]

[0203]

[0204] As shown in Table 2, the imidization rate of the polyimide precursor in the polyimide precursor compositions used in Examples 1-16 was 10 mol% or more and 100 mol% or less relative to the total amount of structural units in the polyimide precursor. In Examples 1-16, the haze was 1.0% or less. Therefore, the polyimide films obtained in Examples 1-16 exhibited excellent transparency. In Examples 1-16, the internal stress was 28 MPa or less. Therefore, the polyimide films obtained in Examples 1-16 were able to reduce internal stress.

[0205] As shown in Table 3, the imidization rate of the polyamic acid in the polyamic acid solution used in Comparative Examples 1-15 was 0 mol% relative to the total amount of structural units in the polyamic acid. The polyamic acid used in Comparative Example 16 did not have a specific zeolite structure. In Comparative Examples 1-15, the internal stress exceeded 28 MPa. Therefore, the polyimide films obtained in Comparative Examples 1-15 could not reduce the internal stress. In Comparative Example 16, since the polyimide precursor composition had gelled, the internal stress could not be measured.

[0206] The results above show that the polyimide film obtained from the polyimide precursor composition of the present invention can improve transparency and reduce internal stress.

Claims

1. A polyimide precursor composition comprising a polyimide precursor and an organic solvent, The polyimide precursor has structural units represented by the following general formula (1) and the following general formula (2). The content of the structural units represented by the following general formula (2) is 10 mol% or more and 100 mol% or less relative to the total amount of structural units in the polyimide precursor. In the general formulas (1) and (2), X comprises one or more groups selected from the group consisting of a tetravalent organic group represented by chemical formula (3) and a tetravalent organic group represented by chemical formula (4), and Y comprises one or more groups selected from the group consisting of a divalent organic group represented by chemical formula (5) and a divalent organic group represented by chemical formula (6).

2. The polyimide precursor composition according to claim 1, wherein, The content of one or more residues selected from the group consisting of the divalent organic groups represented by chemical formula (5) and the divalent organic groups represented by chemical formula (6) is 50 mol% or more and 100 mol% or less, relative to the total amount of diamine residues in the polyimide precursor.

3. The polyimide precursor composition according to claim 1, wherein, In the general formulas (1) and (2), X further comprises: one or more of the following groups: a tetravalent organic group represented by the following chemical formula (7), a tetravalent organic group represented by the following chemical formula (8), a tetravalent organic group represented by the following chemical formula (9), a tetravalent organic group represented by the following chemical formula (10), and a tetravalent organic group represented by the following chemical formula (11).

4. The polyimide precursor composition according to claim 3, wherein, The content of one or more residues selected from the group consisting of the tetravalent organic group represented by chemical formula (7), the tetravalent organic group represented by chemical formula (8), the tetravalent organic group represented by chemical formula (9), the tetravalent organic group represented by chemical formula (10), and the tetravalent organic group represented by chemical formula (11) is 5 mol% or more and 95 mol% or less, relative to the total amount of tetracarboxylic acid dianhydride residues in the polyimide precursor.

5. The polyimide precursor composition according to claim 1, wherein, The organic solvent is one or more selected from the group consisting of N-methyl-2-pyrrolidone, 1-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, N,N-dimethylpropionamide, N,N-diethylformamide, and 1,3-dimethyl-2-imidazolinone.

6. A polyimide film comprising a polyimide having structural units represented by the following general formula (2), The coefficient of linear expansion of the polyimide film is below 30 ppm / K. In the general formula (2), X comprises one or more groups selected from the group consisting of tetravalent organic groups represented by chemical formula (3) and tetravalent organic groups represented by chemical formula (4), and Y comprises one or more groups selected from the group consisting of divalent organic groups represented by chemical formula (5) and divalent organic groups represented by chemical formula (6).

7. The polyimide film according to claim 6, wherein, The content of one or more residues selected from the group consisting of the divalent organic groups represented by chemical formula (5) and the divalent organic groups represented by chemical formula (6) is 50 mol% or more and 100 mol% or less, relative to the total amount of diamine residues in the polyimide. In the general formula (2), X further comprises: one or more of the following groups: a tetravalent organic group represented by the following chemical formula (7), a tetravalent organic group represented by the following chemical formula (8), a tetravalent organic group represented by the following chemical formula (9), a tetravalent organic group represented by the following chemical formula (10), and a tetravalent organic group represented by the following chemical formula (11). The content of one or more residues selected from the group consisting of the tetravalent organic group shown in chemical formula (7), the tetravalent organic group shown in chemical formula (8), the tetravalent organic group shown in chemical formula (9), the tetravalent organic group shown in chemical formula (10), and the tetravalent organic group shown in chemical formula (11) is 5 mol% or more and 95 mol% or less, relative to the total amount of tetracarboxylic dianhydride residues in the polyimide.

8. The polyimide film according to claim 6, wherein, The haze level is below 1.0%.

9. A laminate having a support and the polyimide film of claim 6.

10. An electronic device having the polyimide film of claim 6 and electronic components disposed on the polyimide film.

11. An electronic device having a laminate as claimed in claim 9 and electronic components disposed on the polyimide film of the laminate.

12. A method for manufacturing a laminate, said laminate having a support and a polyimide film, The manufacturing method includes the following steps: Step Sa involves forming a coating film containing the polyimide precursor by coating the polyimide precursor composition of claim 1 onto a support; and In step Sb, a polyimide film is formed on the support by heating the coating film obtained in step Sa.

13. A method for manufacturing a polyimide film, wherein, A laminate having a support and a polyimide film is formed by the method of claim 12, and the polyimide film is peeled off from the support.

14. A method for manufacturing an electronic device, wherein, A laminate having a support and a polyimide film is formed by the method of claim 12, and electronic components are formed on the polyimide film.

Citation Information

Patent Citations

  • Copolyimide precursor and copolyimide

    JP2012041530A

  • Polyimide precursor and resin composition including the same, polyimide film and method for manufacturing the same, and laminate and method for manufacturing the same

    JP2014070139A

  • Polyimide precursor and polyimide

    JP2016029177A

  • Polymers for use in electronic devices

    JP2021521284A